Diurnal expansion and contraction of englacial fracture networks revealed by seismic shear wave splitting - Wojciech Gajek (Nature Portfolio, 2021)
Daily variations in seismic S-wave anisotropy reveal the dynamic response of englacial fractures to changing meltwater supply, according to shear wave splitting measurements from a seismometer network on the Rhonegletscher, Switzerland.